2018
DOI: 10.1371/journal.pone.0203260
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry, polarity, and organometallics in solid-phase extracted dissolved organic matter of the Elbe-Weser estuary

Abstract: Dissolved organic matter (DOM) is ubiquitous in natural waters and plays a central role in the biogeochemistry in riverine, estuarine and marine environments. This study quantifies and characterizes solid-phase extractable DOM and trace element complexation at different salinities in the Weser and Elbe River, northern Germany, and the North Sea. Dissolved organic carbon (DOC), total dissolved nitrogen (TDN), Co and Cu concentrations were analyzed in original water samples. Solid-phase extracted (SPE) water sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 95 publications
7
17
0
Order By: Relevance
“…3). Ksionzek et al (2018) measured a reduction in Cu-DOM binding with increasing salinity, which is consistent with our modelling results. Hamilton-Taylor et al (2002) also predicted that Cu-humic binding decreased substantially with increasing ionic strength under typical estuarine conditions, but they did not postulate Ca and Mg binding as a significant factor.…”
Section: Salinitysupporting
confidence: 91%
See 1 more Smart Citation
“…3). Ksionzek et al (2018) measured a reduction in Cu-DOM binding with increasing salinity, which is consistent with our modelling results. Hamilton-Taylor et al (2002) also predicted that Cu-humic binding decreased substantially with increasing ionic strength under typical estuarine conditions, but they did not postulate Ca and Mg binding as a significant factor.…”
Section: Salinitysupporting
confidence: 91%
“…Cu) to colloidal and dissolved organic matter (DOM) is also very important in estuaries because a quite different geochemistry can be observed for these metals compared with the predominantly particleassociated metals (Santschi et al 1997;Tang et al 2002;Illuminati et al 2019). The binding behaviour of individual metals to DOM, and the functional composition of the DOM itself, can also vary with salinity in estuaries (Zhou et al 2016;Ksionzek et al 2018). In addition, pH and inorganic carbon speciation may vary markedly in an estuary as river water, with typically lower pH and alkalinity (except in some calcareous drainage basins), mixes with seawater.…”
Section: Introductionmentioning
confidence: 99%
“…DOC content and pH exert the major controls on Cu partitioning onto riverine DOC-conditioned suspended particulate matter (SPM) (Lu and Allen, 2001). Copper is also the divalent cation with strongest affinities to DOM (Xue and Sigg, 2002;Ksionzek et al, 2018). In a follow-up study, Lu and Allen (2002) found small amounts of strong phenolic Cu binding sites in DOM based on titration data.…”
Section: The Non-conservative Component Of Mixingmentioning
confidence: 99%
“…Cu and Fe behavior could be connected to molecular groups that were not addressed by our method. Future studies could close the gap, for instance through parallel or sequential IMAC (immobilized metal-ion affinity chromatography) protocols that are able to retain metal-specific ligands (Paunovic et al, 2005;Smith et al, 2014), or direct measurement of trace metals in DOM extracts (both in retentate and permeate, Waska et al, 2015;Ksionzek et al, 2018).…”
Section: The Non-conservative Component Of Mixingmentioning
confidence: 99%
See 1 more Smart Citation